2009
DOI: 10.1002/nau.20775
|View full text |Cite
|
Sign up to set email alerts
|

Post void dribbling: Incidence and risk factors

Abstract: There was a significant correlation between PVD and urge incontinence in pre-menopausal patients. The overall incidence and causes of PVD relative to age require further study. Body mass index and genital hiatus length may play an important role in PVD, especially in post-menopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In addition, they also reported that Q max decreased with increases in blood glucose levels and BMI (Chen, Miao, Gao, Wang, & Xu, 2015). However, only one study indicated that BMI was associated with PVR in postmenopausal women (Ablove, 2010) and a study detected a negative correlation between ultrasound-estimated bladder weight and PVR ( r = −0.213, p = .033) in men with LUTS (Bright, Pearcy, & Abrams, 2011), while no study has investigated the association between BMI and PVR in BPH patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they also reported that Q max decreased with increases in blood glucose levels and BMI (Chen, Miao, Gao, Wang, & Xu, 2015). However, only one study indicated that BMI was associated with PVR in postmenopausal women (Ablove, 2010) and a study detected a negative correlation between ultrasound-estimated bladder weight and PVR ( r = −0.213, p = .033) in men with LUTS (Bright, Pearcy, & Abrams, 2011), while no study has investigated the association between BMI and PVR in BPH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Two large cohort studies have indicated obesity is related to the risk of symptomatic BPH (Giovannucci et al, 1994; Kristal et al, 2007), but the influence of body mass index (BMI) on PV, IPSS, and Q max have not yet been conclusively assessed. Besides, post-void residual (PVR) urine is an important index evaluating conditions for any patient presenting with lower urinary tract symptoms (LUTS), and in 2010, a study indicated that BMI and genital hiatus length might play an important role in post-void dribbling, especially in postmenopausal women (Ablove, 2010); however, the association between BMI and PVR in BPH patients remains blurred. Therefore, this study was performed to explore the relationship of BMI with PV, IPSS, Q max , and PVR in Chinese BPH patients.…”
mentioning
confidence: 99%
“…In the Austrian survey, considering women with urinary incontinence, postvoid dribbling was reported to be at least "bothersome" in 24.5% and moderately/severely bothersome in 14.4%, similar to our Postvoid Dribbling and Urine Spraying ORIGINAL RESEARCH n survey that found 13% to be at least moderately bothered by delayed postvoid dribble. 4 In a smaller study by Ablove,5 of 163 women being evaluated for pelvic floor dysfunction, the incidence of postvoid dribbling was 42%. Similar to our study's findings, in Ablove's premenopausal and perimenopausal patients, postvoid dribbling was associated with UUI.…”
Section: Discussionmentioning
confidence: 99%
“…One trial found that, for patients with UUI plus more severe/common postvoid dribbling, anticholinergics resulted in greater reduction of postvoid dribbling episodes compared with placebo 6 . In Ablove's postmenopausal patients, postvoid dribbling also showed an association with age, body mass index, and the length of the genital hiatus 5 . Although some have speculated that postvoid dribbling may result from pelvic floor weakness, indicating a presumed increase with age, 2 Ablove 5 actually suggested a decreased incidence of postvoid dribble with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…Although an integrative review should speak to the level of evidence, in this study it was difficult to select only studies with higher levels of evidence because elements to construct definitions were needed. Therefore, from a total of 1,927 articles identified in the databases, 31 were considered relevant to answering the research question (Ablove, ; Abrams et al., ; Arianyagam, Arianyagam, & Rashid, ; J. Buchanan, & M. Beckmann, ; Chang, ; Chang, Hsieh, & Yang, ; Chapple & Osman, ; Gursoy et al., ; Hansen, Soreid, Darland, & Nilsen, ; Haylen et al., ; Hernandez et al., ; Huang et al., ; Johansson & Christensson, ; Justo, Schwartz, Dvorkin, Gringauz, & Groutz, ; Madersbacher et al., ; Mago et al., ; Malik, Cohn, & Bales, ; Maserejian et al., ; Mulder et al., ; Mulder et al., ; Negro & Muir, ; Nevo, Mano, Livne, Sivan, & Ben‐Meir, ; Oelke, Speakman, Desgrandchamps, & Mamoulaks, ; Osman et al., ; Saaby & Lose, ; Shimoni, Fruger, & Froom, ; Silveira et al., ; Wilson, ). Several additional sources were included in this integrative review: an English language dictionary (Deuter, Bradbery, & Turnbull, ), a publication by the ICS (Abrams et al., ), and a book published by ICS in 2013 (Staskin et al., ).…”
Section: Data Sources/literature Searchmentioning
confidence: 99%